2020
DOI: 10.1080/20008198.2020.1837511
|View full text |Cite
|
Sign up to set email alerts
|

No association between major depression with and without childhood adversity and the stress hormone copeptin

Abstract: Background: Adverse childhood experiences (ACE) are associated with an increased risk of major depressive disorder (MDD) and hypothalamic-pituitary-adrenal (HPA) axis dysregulation. Within the HPA axis, corticotropin-releasing hormone and vasopressin (AVP) synergistically stimulate the release of adrenocorticotropic hormone, which promotes cortisol release. The cleavage product copeptin is produced during AVP synthesis and is a surrogate marker of AVP release. Children with ACE and young adults with depressive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Previous studies have not reported an association between copeptin and ET. We observed altered copeptin levels in adolescents with MDD, with higher copeptin levels in those with MDD compared to those without, which is inconsistent with some earlier studies [50] but aligns with others [51] .…”
Section: The Relationship Between Depression Circadian Rhythm Prefere...contrasting
confidence: 99%
“…Previous studies have not reported an association between copeptin and ET. We observed altered copeptin levels in adolescents with MDD, with higher copeptin levels in those with MDD compared to those without, which is inconsistent with some earlier studies [50] but aligns with others [51] .…”
Section: The Relationship Between Depression Circadian Rhythm Prefere...contrasting
confidence: 99%